The Effect of Using LMS Moodle on Improving Students' Understanding of Algorithms, C++ Programming, and Active Involvement in Informatics Learning at Senior High School X in Bekasi City: A Comparative Study - Mathias Marciano M (MASI Mandiri Edukasi, 2026)
This study aims to compare students’ understanding of algorithms, C++ programming skills, and active engagement in Informatics learning between those who use the Moodle Learning Management System (LMS) and those who do not at SMA X Kota Bekasi. The research employs a quantitative method with a causal comparative design, involving two naturally formed groups based on their use of LMS in classroom learning. Research instruments include a learning outcome test (posttest), programming practice assessment, and a student engagement questionnaire. The results indicate that the Moodle user group demonstrated a higher understanding of algorithms, with an N-Gain score of 0.411 (medium category), compared to the non-user group, which had an N-Gain score of 0.238 (low category). In terms of C++ programming skills, the Moodle group showed more stable, higher average performance, although the Mann-Whitney U test revealed no statistically significant difference (Sig. = 0.165 > 0.05). Meanwhile, student engagement questionnaire results showed that the Moodle group had significantly higher engagement levels, as confirmed by an Independent Samples t-test (Sig. = 0.006; p < 0.05). Overall, the study concludes that there are positive differences in algorithmic understanding and student engagement between Moodle users and non-users, as well as a favorable, though not statistically significant, difference in C++ programming skills.